2020
DOI: 10.1099/ijsem.0.004250
|View full text |Cite
|
Sign up to set email alerts
|

Chryseobacterium vaccae sp. nov., isolated from raw cow's milk

Abstract: The GenBank/EMBL/DDBJ accession number for the 16S rRNA gene sequence of strain xxx is MN328031. The Whole Genome Shotgun project has been deposited in GenBank/EMBL/DDBJ under accession VSWH00000000. Two supplementary tables and three supplementary figures are available with the online version of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Negative The Chryseobacterium genus contains many aquatic, livestock, and poultry pathogens, including human pathogens (Callon et al, 2007;Hsueh et al, 1997Hsueh et al, , 2002. The genus contains 113 pathogenic species, including C. indologenes (Lee et al, 2020).…”
Section: Reaction Item Results Reaction Item Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Negative The Chryseobacterium genus contains many aquatic, livestock, and poultry pathogens, including human pathogens (Callon et al, 2007;Hsueh et al, 1997Hsueh et al, , 2002. The genus contains 113 pathogenic species, including C. indologenes (Lee et al, 2020).…”
Section: Reaction Item Results Reaction Item Resultsmentioning
confidence: 60%
“…The Chryseobacterium genus contains many aquatic, livestock, and poultry pathogens, including human pathogens (Callon et al, 2007; Hsueh et al, 1997, 2002). The genus contains 113 pathogenic species, including C. indologenes (Lee et al, 2020). Reports have indicated that C. indologenes caused septicaemia in Rana pipiens , caused disease in Salmo salar , and infected Oncorhynchus keta (Ilardi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term storage was in 15 % glycerol at −80 °C. The following strains were obtained for comparison: from the USDA-ARS Culture Collection (NRRL), Chryseobacterium vietnamense NRRL B-59550 T [18]; from the Japan Collection of Microorganisms, Chryseobacterium aquifrigidense JCM 14756 T [19], Chryseobacterium cucumeris JCM 31422 T [20], Chryseobacterium gleum JCM 2410 T [21], and Chryseobacterium vaccae JCM 33749 T [22]; from the Korean Collection for Type Cultures: Chryseobacterium artocarpi KCTC 32509 T [23] and Chryseobacterium flavum KCTC 12877 T [24]; and, from the Culture Collection University Of Gothenburg, Chryseobacterium culicis CCUG 58784 T [25] and Chryseobacterium tructae CCUG 60111 T [26]. Physiological and biochemical analysis was investigated using API ZYM, API 20NE, and API 50CH test strips (bioMériux).…”
Section: Methodsmentioning
confidence: 99%
“…**Data from Holmes et al [30]. † † Data from Lee et al [31]. ‡ ‡Data from Carmen Montero-Calasanz et al [32].…”
Section: Chemotaxonomic Analysismentioning
confidence: 99%